2008
DOI: 10.1002/ejoc.200800372
|View full text |Cite
|
Sign up to set email alerts
|

Modular Routes Towards New N,O‐Bidentate Ligands Containing an Electronically Delocalised β‐Enaminone Chelating Backbone

Abstract: Polyketones are synthesised by a transition‐metal‐catalysed copolymerisation of olefins and carbon monoxide. Nickel complexes with N,O‐chelating ligands turned out to be promising catalysts in that field. In this work a series of new N,O ligands with an electronically delocalised β‐enaminone backbone were synthesised and fully characterised. The ligand design was inspired by the ligand found in the most efficient nickel catalyst for polyketone synthesis and developed to a highly modular LEGO®‐like arsenal of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…[6][7][8] β-Aminovinyl ketones with a fluoroalkyl moiety are interesting organic precursors that can be decorated in a number of useful synthetic sequences to produce diverse molecular entities with specific applications. [1,[9][10][11][12][13][14][15][16][17][18][19][20][21] Their potentially broad coordination chemistry [21][22][23][24][25][26][27][28][29] combined with appropriate organic functionalities make them attractive for the design of a new generation of original materials with potential in catalysis, molecular magnetism and therapeutic applications. A series of fluorinated enaminones that bear two independent coordination centres have been obtained, and the crystal structure of a Cu II complex has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] β-Aminovinyl ketones with a fluoroalkyl moiety are interesting organic precursors that can be decorated in a number of useful synthetic sequences to produce diverse molecular entities with specific applications. [1,[9][10][11][12][13][14][15][16][17][18][19][20][21] Their potentially broad coordination chemistry [21][22][23][24][25][26][27][28][29] combined with appropriate organic functionalities make them attractive for the design of a new generation of original materials with potential in catalysis, molecular magnetism and therapeutic applications. A series of fluorinated enaminones that bear two independent coordination centres have been obtained, and the crystal structure of a Cu II complex has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, when using the nonfluorinated cyclohexanecarbonyl chloride (for comparative studies) in this reaction, we found that only N-acylation took place to yield the unwanted [1-cyclohexanecarbonylpyrrolidin-(2E)-ylidene]acetonitrile. [12] Hence, the nonfluorinated analogue of HL 3 remains inaccessible by this method. The complexation of (L 3 ) -to yield the desired nickel complexes 7 or 8 is accomplished by reacting stoichiometric amounts of HL 3 with (SP- (2), respectively, in the presence of sodium bis(trimethylsilyl)-amide as base.…”
Section: Resultsmentioning
confidence: 98%
“…We reported the syntheses of such bidentate N,O ligands containing an electronically delocalised β-enaminonic chelating backbone in a recent paper. [12] The ligands used in this investigation are summarised in Table 1, and the corresponding nickel complexes are shown in Table 2. Complex 3 is already known and structurally characterised.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations